2013
DOI: 10.1007/s00134-013-2826-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of plasma neutrophil gelatinase-associated lipocalin in the early diagnosis of contrast-induced acute kidney injury in critical illness

Abstract: CI-AKI was common in critically ill patients. pNGAL levels were higher in patients with sepsis or previous AKI, but did not help to diagnose CI-AKI any earlier than serum creatinine after CM injection. However, pNGAL could be of interest to detect patients at risk of subsequent RRT requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In SHRs with CI-AKI, the area under the receiver operating characteristic curve (AUROC) value of NGAL is 0.73, which is accepted as a value of failure [6] . In contrast, in humans with CI-AKI, 4 of 8 studies showed an excellent value (0.93-1.0) [39][40][41][42] , 2 of 8 studies showed a good value of NGAL (0.83-0.84) [43,44], and 2 of 8 studies showed a poor value of NGAL (0.63-0.68) [29,45] . In CKD patients undergoing elective coronary angiography with contrast, postprocedural NGAL increases from baseline in each stage of CKD [46] .…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 92%
“…In SHRs with CI-AKI, the area under the receiver operating characteristic curve (AUROC) value of NGAL is 0.73, which is accepted as a value of failure [6] . In contrast, in humans with CI-AKI, 4 of 8 studies showed an excellent value (0.93-1.0) [39][40][41][42] , 2 of 8 studies showed a good value of NGAL (0.83-0.84) [43,44], and 2 of 8 studies showed a poor value of NGAL (0.63-0.68) [29,45] . In CKD patients undergoing elective coronary angiography with contrast, postprocedural NGAL increases from baseline in each stage of CKD [46] .…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 92%
“…In hospitalized patients with AKI, urinary Kim-1 has been shown to predict adverse clinical outcomes such as mortality (29). NGAL is a 25-kDa protein originally isolated from neutrophil secondary granules (30) and is a classic biomarker for the early diagnosis and short-term outcome of AKI. Therefore, in the present study, Kim-1 and NGAL were selected for use in the evaluation of the therapeutic effectiveness of CRRT in septic AKI and investigation of the possible mechanisms.…”
Section: Group a (N=17) Group B (N=21) ------------------------------mentioning
confidence: 99%
“…In the ICU, according to the definition used, this incidence varies from 16 to 31 % [122][123][124][125]. Several other risk factors for kidney injury are usually concomitantly found in critically ill patients (hypotension, sepsis, nephrotoxic drugs), making it difficult to consider contrast media directly and solely responsible for AKI.…”
Section: (Grade 2+) Strong Agreementmentioning
confidence: 99%